2020
DOI: 10.31117/neuroscirn.v3i1.41
|View full text |Cite
|
Sign up to set email alerts
|

MTRR gene variant rs1801394 found in Malaysian patients with neural tube defects

Abstract: Neural tube defects (NTDs) are congenital anomalies resulting from the failure of neural tube closure during embryogenesis. The precise molecular mechanisms underlying this multifactorial disease is poorly understood, although single nucleotide polymorphisms in genes involved in the one-carbon metabolism cycle are believed to contribute towards NTD development. Among them is 5-methyltetrahydrofolate-homocysteine methyltransferase reductase (MTRR). Protein function prediction algorithms (PolyPhen-2, PRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Whilst, in exome datasets of proband SB2A and father of proband SB2A (SB2C), with both heterozygous for EPHA2 variant (rs147977279), 2 different variants in MTRR (rs162036, and rs10380) were also annotated as heterozygous in SB2A but not in SB2C (wildtype). Our previous study on the same cohort revealed that 57% of patients and 83% of parents carried rs1801394 mutation in their MTRR gene, based on either homozygous (G/G) or heterozygous (A/G) genotypes (Tan et al, 2020). In that study, we concluded that MTRR rs1801394 variant may be an NTD risk factor in the Malaysian population based on the prevalence of this variant in other studies and found that its association with NTDs differed across populations worldwide (Tan et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Whilst, in exome datasets of proband SB2A and father of proband SB2A (SB2C), with both heterozygous for EPHA2 variant (rs147977279), 2 different variants in MTRR (rs162036, and rs10380) were also annotated as heterozygous in SB2A but not in SB2C (wildtype). Our previous study on the same cohort revealed that 57% of patients and 83% of parents carried rs1801394 mutation in their MTRR gene, based on either homozygous (G/G) or heterozygous (A/G) genotypes (Tan et al, 2020). In that study, we concluded that MTRR rs1801394 variant may be an NTD risk factor in the Malaysian population based on the prevalence of this variant in other studies and found that its association with NTDs differed across populations worldwide (Tan et al, 2020).…”
Section: Discussionmentioning
confidence: 69%
“…Our previous study on the same cohort revealed that 57% of patients and 83% of parents carried rs1801394 mutation in their MTRR gene, based on either homozygous (G/G) or heterozygous (A/G) genotypes (Tan et al, 2020). In that study, we concluded that MTRR rs1801394 variant may be an NTD risk factor in the Malaysian population based on the prevalence of this variant in other studies and found that its association with NTDs differed across populations worldwide (Tan et al, 2020). Hereto, the polymorphisms in a Eph and ephrin genes, single one-carbon metabolism gene, or planar cell polarity genes could play a limited role in overall NTD risk determination (Greene et al, 2009;Relton et al, 2004;Kibar et al, 2011;Kibar et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, in exome datasets of proband SB2A and the father of proband SB2A (SB2C), who are both heterozygous for EPHA2 variant (rs147977279), two different variants in MTRR (rs162036, and rs10380) were also annotated as heterozygous in SB2A but not in SB2C (wildtype). Our previous study on the same cohort revealed that 57% of patients and 83% of parents carried the rs1801394 variant in their MTRR gene, based on either homozygous (G/G) or heterozygous (A/G) genotypes [ 66 ]. In that study, we concluded that the MTRR rs1801394 variant may be an NTD risk factor in the Malaysian population based on the prevalence of this variant in other studies and that its association with NTDs differed across populations worldwide [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on the same cohort revealed that 57% of patients and 83% of parents carried the rs1801394 variant in their MTRR gene, based on either homozygous (G/G) or heterozygous (A/G) genotypes [ 66 ]. In that study, we concluded that the MTRR rs1801394 variant may be an NTD risk factor in the Malaysian population based on the prevalence of this variant in other studies and that its association with NTDs differed across populations worldwide [ 66 ]. Hereto, the polymorphisms in Eph and ephrin genes, single one-carbon metabolism genes or planar cell polarity genes could play a limited role in overall NTD risk determination [ 10 , 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%